Microplastics in the freshwater and earthbound conditions: prevalence, destinies, impacts and supportable arrangements - Elena Gregoris; Beatrice Rosso; Marco Roman; and Fabiana Corami (Springer, 2023)
An increasing number of researches have been published on MPs’ different freshwater ecosystems worldwide, including lakes, rivers, estuaries, and wetlands in both waters and sediments. Although the literature on plastics in freshwater is growing, data are globally disjointed about the evidence of concentrations of MPs and impacts on environmental freshwater matrices [1]. Besides, the heterogeneity of sampling protocols, methodologies, techniques, and measurement units among different researches makes it challenging to compare results and produce a complete picture of the existing state of understanding [2]. Another critical factor is that MPs<100 μm (SMPs) are often overlooked; less than 20% of reported studies on freshwater environments reported MPs below 20 μm. The sampling and analytical procedures are strictly connected to detecting plastic particles sizes >100 μm. Consequently, most of the reported studies could have undervalued the concentration of SMPs. Thus, improvement in detection technologies and pre-treatments methods could modify the final mean amount of MPs in freshwater environments [3]. Freshwater systems are considered an important source and critical pathway for MP pollution in coastal and marine environments, especially for the point sources close to areas with a high density of population and civilization [4–6]. Research in freshwater environments has detected MPs in Europe, North America, Africa, Asia, and Antarctica. The USA has performed the most research on MPs of all freshwater microplastics studies, followed by China [7]. Regarding water, the most polluted areas are Southeast Asia and Europe, while sediments are also highly contaminated in North Africa and North America [1]. Thus, MPs are widespread pollutants not only in marine systems but also in freshwater systems. Studies on MPs in freshwater systems are mainly conducted in rivers, lakes, and estuaries, while new research has focused on wetlands, stormwater ponds, and reservoirs. However, there is limited knowledge about MPs ...